Murder by Pushing: An Exploratory Analysis of Homicidal Falls From a Height. (September 2018) - Ferguson, Claire; Sutherland, Tiffany
Abstract : Abstract: The difficulty in classifying manner of death in falls from a height provides offenders an opportunity to avoid detection by having a homicide appear otherwise. Twelve fall homicides were qualitatively examined. Results showed that most homicidal falls occurred at remote outdoor locations, were planned by offenders who were in controlling intimate relationships with the victim, and were motivated by gain. Homicide was established using inconsistencies in offender's statements and the physical evidence, inappropriate postoffense behavior, evidence of planning, and improbable alleged victim behavior. Fall homicides pose unique challenges for investigators and may negatively impact on the criminal justice process.